Assessing the psychological distress and coping strategies among academic staff of a university during COVID-19 - Isaiah Owoeye; Toluwani Agunbiade; Adebanke Agboola; Oluwafemi Sanya; Babatope Adebiyi; Furaha Akimanimpaye (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences)
Background: The coronavirus disease 2019 (COVID-19) pandemic has been associated with stress because of its disruption to normal lifestyle. While the resilience of people was challenged, some coping strategies were adopted to maintain balance in the face of the pandemic.